Development of Electronic Student Worksheets Assisted with Wizer.me on Redox Reactions Learning - Pamenang, Fransisca Ditawati Nur; Ngetje, Brigita Febrisilia (Universitas Pendidikan Mandalika, 2024)
Student worksheets serve as valuable teaching materials facilitating students' learning processes by expanding information on the targeted study topics. In the context of learning redox reactions, Depok 1stState Senior High School exclusively utilizes printed student worksheets. This research focuses on developing electronic student worksheets assisted by the Wizer.me platform for redox reaction material in class, aiming to enhance the efficacy of the learning materials. The research employs a Research and Development (R&D) method, utilizing the 4D development model modified to 3D. Instruments such as interview sheets, validation sheets, and questionnaires were employed, with a sample comprising 10 students from 10th grade. Data analysis was conducted descriptively. The results of the research indicate that 4D models were instrumental in developing electronic student worksheets due to their clearly directed steps or procedures. The developed product exhibits high validity, scoring an average of 84% for both the media and material aspects, with a content validity coefficient exceeding 0.8. Students responded positively to the student worksheet products, rating them high in design (82%), operational and visual communication (83%), resulting in an overall average score of 83%, classified as very practical. The developed product proves effective in supporting the learning of redox reactions.